2019
DOI: 10.1016/j.jml.2019.104031
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the lexical boost with nonhead nouns

Abstract: In five structural-priming experiments, we investigated lexical boost effects in the production of ditransitive sentences. Although the residual activation model of Pickering and Branigan (1998) suggests that a lexical boost should only occur with the repetition of a syntactic licensing head in ditransitive prepositional object (PO)/double object (DO) structures, Scheepers, Raffray, and Myachykov (2017) recently found that it also occurs with the repetition of nouns that are not syntactic heads. We manipulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 44 publications
9
36
1
Order By: Relevance
“…As we noted in the Introduction, the present studies do not allow us to differentiate between a view under which a semantic construction prototype is actually stored in memory (e.g., Abbot‐Smith & Tomasello, 2006) and a view under which it is merely emergent across stored exemplars of the construction (e.g., Ambridge, 2019). Future studies may be able to differentiate between these possibilities by manipulating lexical overlap: If participants show an advantage (whether in comprehension or production) for patterns of verbs and arguments that have occurred frequently in the input, or have been recently presented during priming (e.g., He was killed by… ), this would appear to constitute evidence that exemplars are retained with considerable lexical detail (though the jury is still out with regard to exactly when such lexical boosts occur, and exactly what they mean; e.g., Carminati, van Gompel, & Wakeford, 2019; Scheepers, Raffray, & Myachykov, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As we noted in the Introduction, the present studies do not allow us to differentiate between a view under which a semantic construction prototype is actually stored in memory (e.g., Abbot‐Smith & Tomasello, 2006) and a view under which it is merely emergent across stored exemplars of the construction (e.g., Ambridge, 2019). Future studies may be able to differentiate between these possibilities by manipulating lexical overlap: If participants show an advantage (whether in comprehension or production) for patterns of verbs and arguments that have occurred frequently in the input, or have been recently presented during priming (e.g., He was killed by… ), this would appear to constitute evidence that exemplars are retained with considerable lexical detail (though the jury is still out with regard to exactly when such lexical boosts occur, and exactly what they mean; e.g., Carminati, van Gompel, & Wakeford, 2019; Scheepers, Raffray, & Myachykov, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown a robust effect of structural priming in language comprehension (Arai et al, 2007;Branigan et al, 2005;Thothathiri & Snedeker, 2008) and production (Bock, 1986a(Bock, , 1986bBock & Loebell, 1990;Hartsuiker et al, 2008;Pickering & Branigan, 1998). Importantly, structural priming is even stronger if the prime and target have the same verb; this is called the lexical boost effect (see Bernolet et al, 2014;Carminati et al, 2019;Hartsuiker et al, 2008;Rowland et al, 2012;Scheepers et al, 2017). According to Pickering and Branigan's (1998) account of lexical-syntactic representations, this lexical boost effect is restricted to the repetition of the syntactically licensing head (e.g., the lemma node of the verb "geven" in Figure 1).…”
Section: Using Structural Priming To Tap Into Representations Of Particle Verbsmentioning
confidence: 99%
“…Thus, when the same verb is used again in the target sentence, more activation than usual will flow to the combinatorial node that was used in the prime. There should not be a boost from the repetition of other arguments (e.g., agent, recipient, and theme, Carminati et al, 2019; but see Scheepers et al, 2017) as these arguments are not directly connected to the combinatorial node. Additionally, the priming effect can also be boosted by semantic or phonological overlap between prime and target, but these boosts are much weaker than that of verb repetition (Bock, 1986a(Bock, , 1987Cleland & Pickering, 2003;Santesteban et al, 2010).…”
Section: Using Structural Priming To Tap Into Representations Of Particle Verbsmentioning
confidence: 99%
“…Many studies have shown a robust effect of structural priming in language comprehension (Arai et al, 2007;Branigan et al, 2005;Thothathiri & Snedeker, 2008) and production (Bock, 1986a(Bock, , 1986bBock & Loebell, 1990;Hartsuiker et al, 2008;Pickering & Branigan, 1998). Importantly, structural priming is even stronger if the prime and target have the same verb; this is called the lexical boost effect (see Bernolet et al, 2014;Carminati et al, 2019;Hartsuiker et al, 2008;Rowland et al, 2012;Scheepers et al, 2017). According to Pickering and Branigan's (1998) account of lexical-syntactic representations, this lexical boost effect is restricted to the repetition of the syntactic licensing head (e.g., the lemma node of the verb "geven" in Figure 1).…”
Section: Using Structural Priming To Tap Into Representations Of Partmentioning
confidence: 99%
“…According to Pickering and Branigan's (1998) account of lexical-syntactic representations, this lexical boost effect is restricted to the repetition of the syntactic licensing head (e.g., the lemma node of the verb "geven" in Figure 1). There should not be a boost from the repetition of other arguments (e.g., agent, recipient, and theme, Carminati et al, 2019). Additionally, the priming effect can also be boosted by semantic or phonological overlap between prime and target, but this boost is much weaker than that of verb repetition (Bock, 1986a(Bock, , 1987Cleland & Pickering, 2003;Santesteban et al, 2010).…”
Section: Using Structural Priming To Tap Into Representations Of Partmentioning
confidence: 99%